2013
DOI: 10.1159/000355708
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Irradiation with High Tangent Fields for Clinically Node-Negative Breast Cancer: Can 3-D Conformal Radiotherapy with a Field-in-Field Technique Better Control the Axilla?

Abstract: Background: The target volume for postoperative breast irradiation is the remaining breast tissue, and the axillary region is not an intentional target volume. Patients and Methods: Between 2001 and 2009, eligible women with pT1-2cN0/pN0(sn) breast cancer underwent breast-conserving therapy without axillary dissection. Treatment outcomes between 2 radiotherapy planning groups, high tangent fields with 2-dimensional (2-D) simulation-based planning and 3-dimensional (3-D) computed tomography-based planning with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Great emphasis was again given to locoregional treatment aspects, with observations that surgery is being further minimized but radiotherapy appears to be becoming more aggressive [4], and surgical tactics do not change much after neoadjuvant therapy. The impact of a rising number of molecular testing tools was assessed, both for judging prognosis of early and late metastasis risk, but also for prediction of therapy benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Great emphasis was again given to locoregional treatment aspects, with observations that surgery is being further minimized but radiotherapy appears to be becoming more aggressive [4], and surgical tactics do not change much after neoadjuvant therapy. The impact of a rising number of molecular testing tools was assessed, both for judging prognosis of early and late metastasis risk, but also for prediction of therapy benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the degree of incidental lymph node irradiation varied between the patients from 12.1 ± 19.2% of the prescribed dose (patient III) to 64.8 ± 17.8% of the prescribed dose (patient II). Differently from our study, most previous studies estimated the dose distribution in the lymph node areas as defined by RTOG or ESTRO guidelines [ 5 , 6 , 9 , 11 , 24 , 25 ]. However, these guidelines define a treatment volume and do not necessary reflect the whole axillary lymph node drainage system and both primary lymph node metastases and lymph node recurrences occur outside the ESTRO and RTOG margins [ 16 , 26 ].…”
Section: Discussionmentioning
confidence: 85%
“…Current guidelines recommend the omission of ALND in case of 1) negative SLNB, 2) micrometastases seen in SLN, or 3) 1–2 positive lymph nodes and T1–2 tumors after BCS without preoperative chemotherapy and planned whole-breast RT [ 5 ]. According to these recommendations, residual tumor cells in the axillary lymph nodes must be expected in a relevant number of patients prior to whole-breast irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in doses to the breast between 2D and 3D-based plans. Sanuki et al 21 reported that the 3D-based HTRT improved axillary control compared with 2D-based HTRT.…”
Section: Discussionmentioning
confidence: 99%